Analisis Kinerja Supply Chain pada Agroindustri Kopi - Satria Iman Gea Putra; Fiona Niska Dinda Nadia; Eka Bambang Gusminto; Didik Pudjo Musmedi (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2019)
Research question’s will be answered in this study is how’s the supply chain performance of coffee processing company UD